Challenges in managing papillary carcinoma thyroid coexisting with hyperthyroidism - case report and review of literature - Yadav, Deepak; Maharjan, S.; Dangol, B.; GC, A.; Shrestha, N.; Nepal, A.; Bhandary, S.; KC, S. (Nepalese Journal of ENT Head and Neck Surgery, 2017)
Papillary carcinoma of thyroid can rarely coexistwith hyperthyroidism and the reported incidence varies widely across the literature. It requires very high degree of suspicion to recognise the malignant nodule preoperatively. We are presenting a case that was initially being treated with carbimazole for hyperthyroidism and he was found to have papillary carcinoma of thyroid on FNAC from cold nodule detected in thyroid scan, probably the first case report from Nepal. Totalthyroidectomy with level VI neck dissection followed by radioiodine ablation was performed. The approach to thyroid nodule in hyperthyroid patients is no different than euthyroid or hypothyroid patients as the risk of malignancy is similar.Thyroid scan is useful for classifying the different causes of hyperthyroidism and hence its management but for characterisation of nodulein terms of benign or malignant, ultrasonography is superior. Fine needle aspiration cytology of any suspicious nodule, in patient with hyperthyroidism,should be advised.